EVALUATION OF MUTAGENIC EFFECT (ANTIMUTAGENIC) OF DALBERGIA LATIFOLIA ON SWISS ALBINO MICE - Pkm, Nagarathna; Kumar Yadav, Chandrajeet; Yadav, Saroj Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Dalbergia latifolia Roxb. (Family: Fabaceae) is a traditional herb, contain latinone andÂ Â Â Â dalcriodain flavonoid having excellence medicinal value8. Thepresentstudy wasdesignedtoevaluatetheanti-mutagenicpotentialofMethanolic extractof Dalbergia latifolia,usingmicronucleus(MN)andchromosomalaberration(CA)assay inmice bonemarrow.Theanti-mutageniceffectofDalbergia latifoliawasassessed usingcyclophosphamideMNformationandCAinmice.Theanimalswerepre-treatedwiththe MethanolicextractofDalbergia latifoliaorallyattwodosesof100, 200mg/kgbody weightforsevendays.InMNandCAtestthetwodosesprovidedprotectionwhengiven24hrs priortoasinglei.padministrationofcyclophosphamide(100mg/kgbodyweight). Theseresults demonstrate thatMethanolic extractofDalbergia latifoliahas got anti-mutagenic potential. Keywords: Dalbergia latifolia, Methanolic extract, anti-mutagenic activity